Last Zombie: Inferno #3 - Keene, Brian (Antarctic Press, 2012)
As the team struggles to survive their horrific present-wildfires, vicious marauders, survivors both vengeful and just desperate, and of course, the remaining zombie threat-their various pasts still haunt them. Planters recalls how his family died. Ian remembers the last time he saw his fiancée, Jennifer. Each must face the demons inside him or her to focus on making it through the ones outside!